Phase transition for the dilute clock model - Armendáriz, María Inés (2015)
We prove that phase transition occurs in the dilute ferromagnetic nearest-neighbour q-state clock model in ℤd, for every q ≥ 2 and d ≥ 2. This follows from the fact that the Edwards-Sokal random-cluster representation of the clock model stochastically dominates a supercritical Bernoulli bond percolation probability, a technique that has been applied to show phase transition for the low-temperature Potts model. The domination involves a combinatorial lemma which is one of the main points of this article.